Be-Fast Faster and Fastest - Tamrakar, Karuna (Eastern Green Neurosurgery, 2019)
Annual incidence of stroke is 2.5%/1000 people or 200000 stroke /year. Every 5 seconds undergo stroke all over the world. 15-20 % die in first month of brain attack and 75% lives with focal neurological deficit. Ischemic stroke is the most common (85%) after hemorrhagic stroke and subarachnoid hemorrhage (15%). Among all 5 subtypes, large artery atherosclerosis, cardio embolism, small vessel occlusion, stroke of other determined etiology, undetermined etiology, ischemic stroke carries poor prognosis of increasing morbidity and mortality. Window of opportunity is a critical time that need to be addressed to reverse neurological stroke symptoms either partially or completely through active interventional approaches either noninvasive or invasive methods. Thrombolysis has radically changed the prognosis of acute ischemic stroke. Intravenous thrombolytic therapy with recombinant tissue plasminogen activator (rtPA) is effective in reducing the neurological deficit. Time is brain, either you be fast or faster and fastest, early or timely reperfusion therapy within a time frame of 4.5 hours helps to restore normal neurological function.